PERKAWINAN DI BAWAH UMUR DALAM HUKUM ADAT BALI DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - , Loresta Cahyaning Lintang, Rama Pramu Wicaksono (PARENTAL, 2015)
AbstractOne indicator of a rule or law is said to be good with legal certainty. Law No. 1 of 1974 on Marriage is one form of unification of law which is a follow up of the existence of legal pluralism with a variety of customary law that developed in the community. Purpose of Marriage Act is to create a society that is the rule of law and legal certainty for the people who are bound by marriage with the diversity of culture and the existence of customary law are still inherent in the culture in Indonesia. Where problems in the Marriage Act contained in the validity of underage marriage in Article 7 paragraph (1) and paragraph (2) of the Act 1 of 1974 that "(1) Marriage is only allowed when the man reaches the age of 19 (nine twelve) years and the woman has reached the age of 16 (sixteen) years, (2) In the case of irregularities in paragraph (1) of this section may request a dispensation to court or other official requested by both parents the man or the woman ". This condition is deviated by Act No. 23 of 2002 on Child Protection in Article 26 paragraph (1) letter c, which states that "Parents have the duty and responsibility to prevent marriage at the age of children". Revision of the Marriage Act is very necessary, especially regarding the dispensation of the court and marry the age limit given the confusion between the Marriage Act with Child Protection Act.Keywords: marriage, custom, child protection